The miraculous character in the novel "Hamut" by the novelist Wafaa Abdel-Razzaq (Journal of the College of Basic Education, 2022)
The fictional character in all its dimensions is only an imaginary element that intersects with the concept of the real character according to the artistic vision that guides the narrative text. Beyond the laws of reality and nature, the writers of the modern novel used them to express the human crisis to break the monotony that dominated the reader's taste and fertilize his imagination with the cultural and intellectual information that the miraculous narrative text enjoys on the one hand. And creating fun, magic and surprise for him through penetration into worlds of miraculous imagination that completely intersect with the real and familiar world on the other hand, which calls for expanding the interpretive horizon of the text by opening the way to the symbolic meaning, as well as understanding the writer’s vision through the characters of his novel, which is the main key To reveal the hidden aspects of the narrative work. The miraculous feature dominates in the novel “Hamut” by the novelist Wafaa Abdul Razzaq, and our research has monitored this feature on several levels of the text structure, perhaps the most prominent of them: the relationship of miraculous characters with the event and the relationship of miraculous characters with the place, and standing on it with criticism and analysis.